A missing component of Arctic warming: black carbon from gas flaring. (6th September 2019) - Cho, Mee-Hyun; Park, Rokjin J; Yoon, Jinho; Choi, Yonghan; Jeong, Jaein I; Labzovskii, Lev; Fu, Joshua S; Huang, Kan; Jeong, Su-Jong; Kim, Baek-Min
Abstract: Gas flaring during oil extraction over the Arctic region is the primary source of warming-inducing aerosols (e.g. black carbon (BC)) with a strong potential to affect regional climate change. Despite continual BC emissions near the Arctic Ocean via gas flaring, the climatic impact of BC related to gas flaring remains uncertain. Here, we present simulations of potential gas flaring using an earth system model with comprehensive aerosol physics to show that increases in BC from gas flaring can potentially explain a significant fraction of Arctic warming. BC emissions from gas flaring over high latitudes contribute to locally confined warming over the source region, especially during the Arctic spring through BC-induced local albedo reduction. This local warming invokes remote and temporally lagging sea-ice melting feedback processes over the Arctic Ocean during winter. Our findings imply that a regional change in anthropogenic aerosol forcing is capable of changing Arctic temperatures in regions far from the aerosol source via time-lagged, sea-ice-related Arctic physical processes. We suggest that both energy consumption and production processes can increase Arctic warming.